2012
DOI: 10.1002/ceat.201100534
|View full text |Cite
|
Sign up to set email alerts
|

Sorption‐Enhanced Steam Reforming of Ethanol: Thermodynamic Comparison of CO2 Sorbents

Abstract: A thermodynamic analysis is performed with a Gibbs free energy minimization method to compare the conventional steam reforming of ethanol (SRE) process and sorption-enhanced SRE (SE-SRE) with three different sorbents, namely, CaO, Li 2 ZrO 3 , and hydrotalcite-like compounds (HTlc). As a result, the use of a CO 2 adsorbent can enhance the hydrogen yield and provide a lower CO content in the product gas at the same time. The best performance of SE-SRE is found to be at 500°C with an HTlc sorbent. Nearly 6 moles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 49 publications
1
27
0
Order By: Relevance
“…It is possible to use such simplification because the hydrogen produced by the reforming reactions is consumed by the electrochemical reaction and because of the high value of its equilibrium constant in the operating conditions considered [32]. In fact many studies have shown that the ethanol steam reforming reaction is driven to completion using appropriate catalysts [33][34][35].…”
Section: Burner-reformermentioning
confidence: 99%
See 1 more Smart Citation
“…It is possible to use such simplification because the hydrogen produced by the reforming reactions is consumed by the electrochemical reaction and because of the high value of its equilibrium constant in the operating conditions considered [32]. In fact many studies have shown that the ethanol steam reforming reaction is driven to completion using appropriate catalysts [33][34][35].…”
Section: Burner-reformermentioning
confidence: 99%
“…The total exergy at a specific position (e.g., compressor outlet) has been estimated from Equation (34) and is the sum of the physical and chemical exergy of the components that are associated with their physical and chemical properties, respectively. An exergy balance for a control volume at steady state is formulated to calculate exergy destruction D E  using Equation (35). Exergy efficiency is referred to the exergetic potential of the primary fuel (standard exergy of ethanol) and is expressed through Equation (36) …”
Section: Exergy Analysis Of the Systemsmentioning
confidence: 99%
“…One way of overcoming these drawbacks is to capture the CO 2 with a sorbent (Chen et al, 2009;Comas et al, 2004;Cunha et al, 2012Cunha et al, , 2013Cunha et al, , 2014Ding and Alpay, 2000;Lee et al, 2004;Lysikov et al, 2008;Wu et al, 2012;Wu et al, 2014aWu et al, , 2014bWu et al, , 2014c by adsorption-reaction. This alternative can supply heat since reactions of CO 2 and water with the sorbent are both exothermic, remove the CO 2 and inhibit the CO formation, all at the same time.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, hydrogen produces a very low content of contamination and can be used to generate electricity in fuel cells . Hydrogen can be produced using diverse techniques (like steam reforming , autothermal reforming , , oxidative reforming , , and pyrolysis ) and from different feed sources such as natural gas, crude oil, naphtha, and other feedstocks like acetic acid, bio‐oil , , ethylene glycol , glycerol , methanol , , , and ethanol . Among the different procedures and feedstocks for hydrogen production, ethanol steam reforming (ESR) has been the subject of numerous studies and can produce a high level of hydrogen , , .…”
Section: Introductionmentioning
confidence: 99%